Economic self-sufficiency (ESS) as a barrier to health self-sufficiency (HSS) for Burmese refugees in the United States: a culture-centered analysis - Kumar, Rati (Frontiers in Communication, 2024)
From displacement to resettlement, Burmese refugees bear high disease burdens; first as forced migrants escaping conflict and then as second-class citizens in host countries like the United States. This relegation of refugee bodies to the margins upon resettlement, warrants an examination of the contradictions of the process as a humanitarian enterprise yet in violation of the United Nations Sustainable Development Goal 10 of Reduced Inequalities, particularly through a health inequities lens. In the present study, the researcher conducted 15 semistructured in-depth interviews with key stakeholders within the resettlement ecosystem of the city of Indianapolis, Indiana in the U.S., including Burmese community members, leaders, and health practitioners. Narrative data reveal an inverse relationship between the federally mandated metric of economic self-sufficiency (ESS) defined as job placement upon resettlement, and health self-sufficiency (HSS) defined as the ability to meaningfully engage with healthcare structures and resources. Participants articulate the precarious nature of such low-wage employment in predatory industries like meatpacking, requiring little to no language or vocational training and subjecting refugee employees to coercive practices including mandatory overtime. These practices are outlined as both dangerous to the health of employees and detracting from their time resources which would otherwise be allocated toward linguistic and vocational training -both required for socioeconomic mobility, as well as to meaningfully navigate labyrinthian healthcare structures. Faced with these structural constraints, Burmese community members demonstrate health self-sufficiency through a combination of treatment with over-the-counter (OTC) medications, traditional healing practices, and by activating familial and community networks as communal resources for accessing healthcare structures.